Road to Avonlea. The complete sixth season [videorecording (DVD)] - Sullivan, Kevin, 1955-; Burroughs, Jackie; Ruffman, Mag; Zamprogna, Gema; Montgomery, L. M. (Lucy Maud), 1874-1942 (Sullivan Entertainment, Inc., 2012)
This 4-disc set, which includes all 13 episodes of the sixth season of this award winning series, is now available for the very first time on DVD in a Remastered format. In this season, the community continues to develop: dealing with the characters moving on in their lives and new romances beginning.